Renal manifestations in tuberous sclerosis patients: two case reports - Oke Rina Ramayani; Rosmayanti Rosmayanti; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society Publishing House, 2013)
Tuberous sclerosis (TS) is a neurocutaneous disorder, characterized by mental retardation, epilepsy, and facial angiofibromas. The incidence has been estimated to be 1 case per 6000 live births. Although rare, this disorder is a cause of mental retardation with severe epilepsy.1 Scientists have found manifestations of this disorder not only in brain and skin, but also in the eyes, heart, lungs, and kidneys, so it has been renamed tuberous sclerosis complex (TSC).